Thermal performance of cooling strategies for asphalt pavement: a state-of-the-art review - Aletbaa, Salam Ridha Oleiwi; Norhidayah, Abdul Hassan; Putra Jaya, Ramadhansyah; Eeydzah, Aminudin; Mohd Zul Hanif, Mahmud; Azman, Mohamed; Ahmed Abdulameer, Hussein (Elsevier B.V., 2021)
Asphalt pavements absorb and store more heat than natural surfaces. Thus, high temperatures are emitted from conventional asphalt pavements, subsequently releasing heat into the atmosphere and emitted from conventional asphalt pavements, subsequently releasing heat into the atmosphere and provision of additives and materials, surface coating and layer design, have been introduced to reduce the impact of UHI. This article provides a detailed review of the thermal properties of these mitigation measures in the context of cool asphalt pavements. The literature can be divided into three segments.